Growth and Carbon Accumulation of Pioneer and Non-pioneer Native Trees of the Atlantic Forest in Urban Afforestation - Milagre, Jocimar Caiafa; Mendes, Lucas José; Sperandei, Álisson Pacheco; Zanchi, Thaís Luz; Morais Júnior, Vicente Toledo Machado de; Tabaldi, Luciane Almeri (Fronteira: Journal of Social, Technological and Environmental Science, 2026)
The growth and carbon (C) sequestration capacity of native trees depend on environmental factors and the intrinsic characteristics of each species. In urban environments, there is a gap in the comparative understanding of the potential for growth and C sequestration between pioneer and non-pioneer tree species. Therefore, the objective of this study was to assess the growth and C accumulation in the aboveground biomass of pioneer and non-pioneer tree species in urban afforestation. Using forest inventory data, the average annual increments in diameter (AAIDBH), height (AAIH), and C (AAIC) were calculated and compared between ecological groups and species in the urban afforestation of the Federal Institute of Espírito Santo. The pioneer group exhibited higher AAIDBH and AAIC, but no significant difference was found between groups for AAIH. Among species, AAIDBH, AAIH, and AAIC varied considerably, with the pioneer species Cenostigma pluviosum, Enterolobium contortisiliquum, and Schizolobium parahyba showing great potential in storing C in aboveground biomass. Given the interspecific variation, intrinsic characteristics must be considered when selecting species to maximize C sequestration in urban environments. The results of this study highlight the influence of ecological group and the individual characteristics of species on C sequestration and can guide urban afforestation planting and management strategies aimed at mitigating greenhouse gas emissions.